Optimizing Banking Investments: Financial technology, Rates, Dividends & CSR Impact - Pujayanti, Putu Gita; Musmini, Lucy Sri; Sujana , Edy (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This study aims to provide empirical evidence on the influence of Financial Technology, interest rates, and dividend policy, all of which are significant factors in investment decision-making, with Corporate Social Responsibility (CSR) as a moderating variable. The study employs a quantitative approach and multiple linear regression analysis. The research sample consists of 47 banking companies listed on the Indonesia Stock Exchange (IDX), with 80 secondary data points collected from 16 samples over the 2019-2023 period. The novelty of this research lies in utilizing CSR as a moderating variable and employing STATA as the testing tool. The findings reveal that Financial Technology and interest rates do not have a significant impact on investment decisions, and CSR is not effective in moderating the relationships between Financial Technology, interest rates, and dividend policy. However, dividend policy has a significant influence on investment decisions. These findings provide valuable insights for company management, serving as a foundation for more informed investment decision-making processe.